Mass production of the entomopathogenic nematode, Steinernema carpocapsae on Tenebrio molitor and Spodoptera litura - HERI PRABOWO; SRI ADIKADARSIH; JANIS DAMAIYANI (Society for Indonesian Biodiversity, 2019)
Abstract. Authors. 2019. Mass production of the entomopathogenic nematode, Steinernema carpocapsae on Tenebrio Molitor and Spodoptera litura. Biodiversitas 20: 1344-1349. Steinernema carpocapsae is the most developed biological agents to control pests nowadays, to support this nematode as a biological agent mass production technique is required. S. carpocapsae can be produced via in vivo methods. In vivo production has some advantages, such as cheap, easy, and sustainable to be developed in small farm agriculture. The purpose of this research was to evaluate the mass production of S. carpocapsae using Tenebrio molitor and Spodoptera litura larvae as hosts. Twenty-five last instar larvae were inoculated with different concentrations of infective juvenile (IJ) (e.g., 100, 200, 300 and 400 IJ/larvae) of S. carpocapsae Asembagus. The production of S. carpocapsae with concentrations of 100, 200, 300 and 400 IJ/larvae on T. molitor and S. litura showed 3.62x103; 6.29x103; 1.13x104; 1.52x104; 1.13x104; 1.46x104; 1.54x104; and 1.94x104 IJ/larvae, respectively. The IJ harvest from T. molitor and S. litura shows the longest body length for IJ at a concentration of 400 IJ/larva of 437.48µm and 591.42µm, respectively. This study indicates that T. molitor and S. litura can be used to produce S. carpocapsae. The production of S. carpocapsae with a concentration of 400 IJ / larvae on T. molitor and S. litura showed the highest total yield and body length of IJ.